Perdebatan Kepentingan Kebijakan Digitalisasi Penyiaran di Indonesia (Studi Kasus Perumusan Kebijakan Digitalisasi Penyiaran pada RUU Penyiaran di DPR 2009-2014 dan 2014-2019) [Interest Disputes of Broadcasting Digitalization Policy in Indonesia] - Ahmad Budiman (Jurnal Politica, 2020)
The formulation and discussion on broadcasting digitalization, as one of the aspects of the Revised Broadcasting Bill, has been well underway since the Parliamentary Period of 2009-2014, and continued in the following Period of 2014-2019. The long period of deliberation of the policy shows that it tries to accommodate many interests. The research question raised in this study is concerned with the contestation arising in the formulation of broadcasting digitalization policy in Indonesia. This study aims to describe the research question regarding the debate over differing interests that occurred in formulating broadcasting digitalization policy in Indonesia. The research method used in this study is a case study qualitative method. Based on the results of the study, in the 2009-2014 period, a debate of interests occurred between the House and the Government, with regard to the rightful provider of multiplex services, has impacts on different definitions of broadcasting. The House maintains that multiplex provider rights should be given to multiplex broadcast providers (LPPM), whereas the Government believes that the rights should be given to IPP-licensed broadcasters. Commission I of the House in the 2014-2019 period formulated the policy of broadcasting digitalization in detail, especially with regard to the matter of the Government’s obligation to formulate the frequency allocation map in every broadcast area, migration model, ASO in every broadcast area and at the national level, digital dividend, and multiplexing fees. The proposed migration model was the single mux model, but it was opposed by the Legislation Committee of the House (Baleg), which proposed the hybrid mux migration model. Baleg believed that the single mux model would potentially create monopolistic practices. Furthermore, the state-owned TVRI has not been equipped with up-to-date broadcasting infrastructure and high-skilled human resources. Certainty in the frequency allocation map calculation in every broadcasting area, prospective digital dividend, and the prospect of broadcast companies must be the main foundation in determining the most appropriate digital migration model in Indonesia. It is certainly not impossible if Indonesia may even have its own unique migration model. Together, the House and the Government have to discuss and finish the Bill on Broadcasting as soon as possible for broadcasting digitalization to take place, for the benefit of the people and the nation of Indonesia.AbstrakPerumusan dan pembahasan kebijakan digitalisasi penyiaran yang menjadi salah satu materi dari perumusan penggantian UU Penyiaran, sudah dilakukan sejak DPR periode 2009-2014 dan dimulai kembali pada DPR periode 2014-2019. Lamanya perumusan dan pembahasan kebijakan digitalisasi penyiaran, menunjukkan materi ini memang sangat sarat kepentingan. Pertanyaan penelitian yang diajukan dalam penelitian ini yaitu bagaimana kontestasi perdebatan kepentingan yang terjadi dalam merumuskan kebijakan tentang digitalisasi penyiaran di Indonesia? Penelitian ini bertujuan mendeskripsikan pertanyaan penelitian mengenai kontestasi perdebatan kepentingan yang terjadi dalam merumuskan kebijakan tentang digitalisasi penyiaran di Indonesia. Metode penelitian yang digunakan dalam penelitian ini yaitu metode kualitatif studi kasus mengenai perdebatan kepentingan perumusan kebijakan digitalisasi penyiaran yang terjadi pada DPR periode 2009-2014 dan DPR periode 2014-2019. Berdasarkan hasil penelitian, pada DPR periode 2009-2014, perdebatan kepentingan terjadi antara DPR dengan Pemerintah, terkait dengan siapa yang berhak menjadi penyelenggara multipeksing yang berdampak juga pada definisi penyiaran yang berbeda. DPR tetap menyatakan penyelenggara multipleksing diserahkan kepada lembaga penyelenggara penyiaran multipleksing (LPPM). Sedangkan Pemerintah menyerahkan penyelenggara kepada lembaga penyiaran yang telah memiliki IPP. DPR periode 2014-2019 melalui Komisi I DPR, merumuskan secara rinci kebijakan digitalisasi penyiaran terkait kewajiban Pemerintah untuk menyusun peta alokasi frekuensi di setiap wilayah siar, model migrasi, ASO disetiap wilayah siar dan secara nasional, digital deviden, dan tarif penyelanggaraan multipleksing. Model migrasi yang diajukan yaitu model single mux, namun mendapatkan pertentangan dari Baleg DPR yang mengajukan model migrasi hybrid mux. Baleg menilai single mux berpotensi memunculkan praktek monopoli, insfrastruktur penyiaran TVRI sudah berusia tua, dan kurangnya kemampuan kompetensi SDM yang dimiliki TVRI. Kepastian hitungan peta alokasi frekuensi di setiap wilayah siar, digital deviden yang diperoleh, dan prospek lembaga penyiaran, harus menjadi dasar utama dalam menentukan model migrasi digital di Indonesia. Bisa jadi kita memiliki model migrasi yang khas Indonesia. DPR bersama Pemerintah, harus segera membahas RUU Penyiaran agar kepentingan masyarakat, bangsa, dan negara Indonesia terkait digitalisasi penyiaran benar-benar dapat terwujud.